2017
DOI: 10.1002/cctc.201700037
|View full text |Cite
|
Sign up to set email alerts
|

Disassembling Metal Nanocrystallites into Sub‐nanometric Clusters and Low‐faceted Nanoparticles for Multisite Catalytic Reactions

Abstract: Metal nanocrystallites present saturated atoms, in planes, and unsaturated metal atoms, in corners and vertices, for catalytic applications. However, both sites are spatially complementary and simultaneously excluding for a given particle, thus their number cannot be independently maximized for a catalytic process. Here, it is shown that the independent dosage of Au clusters and metallic Au nanoparticles dramatically improves the catalytic activity of Au for the Sonogashira reaction, enabling the coupling of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
0
9
1
Order By: Relevance
“…To further confirm that sub-nanometer Pt species are the catalytically active species and that the EVOH polymer does not dissolve nor interfere during the reaction, the Heck reaction catalyzed either by PtCl 2 or Pt@EVOH was also monitored by NMR and Fourier transform infrared (FT-IR) spectroscopy (Figures S12–S13). In the NMR experiments, deuterated DMF was used as solvent, and 4-fluoroiodobenzene was chosen as a substrate to follow the reaction not only by 1 H but also by 19 F NMR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further confirm that sub-nanometer Pt species are the catalytically active species and that the EVOH polymer does not dissolve nor interfere during the reaction, the Heck reaction catalyzed either by PtCl 2 or Pt@EVOH was also monitored by NMR and Fourier transform infrared (FT-IR) spectroscopy (Figures S12–S13). In the NMR experiments, deuterated DMF was used as solvent, and 4-fluoroiodobenzene was chosen as a substrate to follow the reaction not only by 1 H but also by 19 F NMR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Aryl bromides are also reactive and produce the same products, but with lower yields. It must be noted that EVOH and Au@EVOH cannot perform the Heck coupling at all with any haloarene, in contrast to Pt@EVOH, and that the reaction yields of the desired products are also dependent on the type of substituents, even though the oxidative addition is not the only RDS.…”
Section: Resultsmentioning
confidence: 99%
“…Taking into consideration that different molecules may be activated on different types of Au species, the combination of metal clusters and nanoparticles has been shown to enhance the activity of either cluster or nanoparticles for the Sonagashira reaction. 541 Following that idea, in a recent work, it has been demonstrated that the combination of Au nanoparticles and clusters shows significantly higher activity than a single type of catalyst for Sonogashira reaction. As described in Figure 107 , supported Au clusters can leach into solution and activate the C–H bond terminal alkynes with the help of base.…”
Section: Comparison Of the Catalytic Behavior Of Single Atoms Nanoclmentioning
confidence: 99%
“… Mechanistic proposal for the Sonogashira coupling with Au clusters and Au Nanoparticles as bifunctional catalyst. Adapted with permission from ref ( 541 ). Copyright 2017 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.…”
Section: Comparison Of the Catalytic Behavior Of Single Atoms Nanoclmentioning
confidence: 99%
See 1 more Smart Citation